Francesco Tra Guerra E Pace: l'evoluzione della figura del santo di Assisi nel discorso pubblico dei cattolici (1911-1918) - Possieri, Andrea (Rivista di storia del cristianesimo, 2025)
The essay reconstructs the evolution of the figure of Saint Francis of Assisi in the public speech of Italian Catholics, focusing on the period between the Italian-Hottoman War and the First World War (1911-1918). In these years, two different images of the Saint were disseminated: an interpretation of St. Francis as a «saint of peace and reconciliation», promoted above all by the Holy See, was contrasted by a representation of the Poverello of Assisi, as a national saint, knight and warrior. Those who contributed most to the construction of the process of nationalization of Saint Francis were the so-called «National Catholics» united by their opposition to the democratic mentality and by their public role played during the two wars. This is the case, for example, of the Franciscan preacher Vittorino Facchinetti, of Egilberto Martire, a representative of the «Gioventù Cattolica», and of Cardinal Carlo Salotti, member of the Congregation of Rites.